2020
DOI: 10.3390/molecules25235693
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Dual Extracellular Regulated Protein Kinases (ERK) and Phosphoinositide 3-Kinase (PI3K) Inhibitors as a Promising Strategy for Cancer Therapy

Abstract: Concomitant inhibition of MAPK and PI3K signaling pathways has been recognized as a promising strategy for cancer therapy, which effectively overcomes the drug resistance of MAPK signaling pathway-related inhibitors. Herein, we report the scaffold-hopping generation of a series of 1H-pyrazolo[3,4-d]pyrimidine dual ERK/PI3K inhibitors. Compound 32d was the most promising candidate, with potent inhibitory activities against both ERK2 and PI3Kα which displays superior anti-proliferative profiles against HCT116 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…16). 51 Compounds 73-75 were foundd to be dual inhibitors of ERK2 and PI3K-a. Compound 74, a potent and very effective ERK and PI3K dual inhibitor, was discovered during preliminary SAR study.…”
Section: Extracellular Regulated Protein Kinases (Erk)mentioning
confidence: 99%
See 2 more Smart Citations
“…16). 51 Compounds 73-75 were foundd to be dual inhibitors of ERK2 and PI3K-a. Compound 74, a potent and very effective ERK and PI3K dual inhibitor, was discovered during preliminary SAR study.…”
Section: Extracellular Regulated Protein Kinases (Erk)mentioning
confidence: 99%
“…The combined inhibition of the MAPK and PI3K signalling pathways has been identied as a viable cancer therapy that effectively overcomes the drug resistance of MAPK signalling pathway inhibitors. 51 Zhang et al reported the scaffold-hopping synthesis of ERK/ PI3K dual inhibitors by replacing 1H-pyrazolo [3,4- 1% inhibitory activity at the concentration of 1 mM on ERK2 and PI3Ka respectively (Fig. 16).…”
Section: Extracellular Regulated Protein Kinases (Erk)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of cross-talks between PI3K signaling and other pathways are thought will guide future combination strategies of using clinically relevant inhibitors in various tumor types ( 72 , 73 ). Overall, the available evidence suggests that drug resistance (intrinsic or acquired) to such targeted therapies results at least in part from negative feedback interactions between these kinases, combined with tumor heterogeneity, cellular state, mutational background, etc.…”
Section: Discussionmentioning
confidence: 99%
“…1H-Pyrazolo [3,4-d]pyrimidine is an important structural fragment present in naturally occurring nucleosides (Formycin A and Formycin B), which have significant antitumor activity [1,2]. Additionally, 1H-pyrazolo [3,4-d]pyrimidines exhibit various biological activities, including antiviral and analgesic activity, treatment of male erectile dysfunction and hyperuricemia, prevention of gout, and many others [1, 3,4]. Functionally substituted 1H-pyrazolo [3,4-d]pyrimidines showed good antibacterial and antiproliferative activity [5].…”
Section: Introductionmentioning
confidence: 99%